Faunas and correlation of the Late Paleozoic rocks of Northeast Greenland. Part I: General discussion and summary - Dunbar, Carl O.; Troelsen, Johs.; Ross, Charles A.; Ross, June Phillips; Norford, Brian (Meddelelser om Grønland, 1962)
Not applicable.